Morning Haiku - Sanchez, Sonia, 1934- (Beacon Press, 2010)
This new volume by the much-loved poet Sonia Sanchez, her first in over a decade, is music to the ears: a collection of haiku that celebrates the gifts of life and mourns the deaths of revered African American figures in the worlds of music, literature, art, and activism. In her verses, we hear the sounds of Max Roach "exploding in the universe," the "blue hallelujahs" of the Philadelphia Murals, and the voice of Odetta "thundering out of the earth." Sanchez sings the praises of contemporaries whose poetic alchemy turns "words into gems": Maya Angelou, Richard Long, and Toni Morrison. And she pays homage to peace workers and civil rights activists from Rosa Parks and Congresswoman Shirley Chisholm to Brother Damu, founder of the National Black Environmental Justice Network. Often arranged in strings of twelve or more, the haiku flow one into the other in a steady song of commemoration. Sometimes deceptively simple, her lyrics hold a very powerful load of emotion and meaning. There are intimate verses here for family and friends, verses of profound loss and silence, of courage and resilience. Sanchez is innovative, composing haiku in new forms, including a section of moving two-line poems that reflect on the long wake of 9/11. In a brief and personal opening essay, the poet explains her deep appreciation for haiku as an art form. With its touching portraits and by turns uplifting and heartbreaking lyrics, Morning Haiku contains some of Sanchez's freshest, most poignant work